Review article: Neonatal Sepsis in Thailand - Thatrimontrichai, Anucha (Folia Medica Indonesiana, 2018)
Neonatal sepsis is a burden around the world and causes high mortality and morbidity as well. Long-term neurodevelopmental disability may occur in survivors. General physicians, pediatricians, and neonatologists need be attentive to the proper diagnosis, starting, de-escalating or stopping empirical antimicrobials therapy in neonatal sepsis. Furthermore, multidrug resistant organisms have emerged among adults, children, and neonates in developing countries. Local epidemiology studies and antimicrobial stewardship programs are important for application of the best and specific treatments. Knowledge, definitions, and clinical practice of neonatal sepsis are updated in this review.